Il turismo a Venezia dal secondo dopoguerra ad oggi - Andrea Zannini (Laboratoire Italien)
In the first half of the 20th century, Venice was one of the main destination for elite tourism in Italy, thanks to the renown seaside resort of the Lido. After the Second World War a new phase started, the age of mass tourism that, together with the general social and economic transformations of the city, deeply changed the life in the historical center, where tourism had become the predominant economic activity. From the eighties, many studies have investigated the social and cultural effects of tourism on the venetian population but, in the meanwhile, a new phase in world tourism was developing. It involved new subjects and altered totally the dimension of the phenomenon.